Alliances, friendships, and alternative structures: Solidarity among radical left activists and precarious migrants in Malmö. (2nd July 2020) - Hansen, Christina
ABSTRACT: This paper examines relations between radical left activists with citizenship and migrants in precarious conditions. It is based on ethnographic fieldwork conducted in 2013–2016 in the city of Malmö, an important site of pro-migrant and anti-racist activism in Sweden. Examples discussed in the paper concern the prevalence of highly educated women among the activists, the engagement of LGBTQ activists, and the fact that many activists themselves have migrant backgrounds. The alliances, friendships, and alternative structures they forge are analyzed with regard to two groups of precarious migrants in Malmö: the so-called undocumented migrants; and the Roma migrants from southeastern Europe. The paper shows how radical activism contributes to a solidarity-based ethnic diversity in the city that opposes the growing anti-immigrant stance in Sweden on the national level.